Robert O. Gjerdingen, Music in the Galant Style (2007) - Adams, Martin (Journal of the Society for Musicology in Ireland, 2009)
A review of Robert O. Gjerdingen, Music in the Galant Style (Oxford: Oxford University Press, 2007), ISBN 978-0-19-531371-0